Paleomagnetism of Siluro-Devonian and Cambrian granitic rocks from the Avalon zone in Cape Breton Island, Nova Scotia - Rao, K. V.; Seguin, M. K.; Deutsch, E. R. (Canadian Journal of Earth Sciences, 1981)
As part of a major study of the Avalon zone in Cape Breton Island, we describe the paleomagnetism of radiometrically well-studied granitic rocks of two generations, representing the Acadian (350–450 Ma) and the Avalonian (520–580 Ma) Orogenies, respectively. Detailed alternating field (AF) and thermal experiments performed on the younger granites indicate that they are characterized by three different mean directions of magnetization in the 10–60 mT coercivity spectra: SE (D = 149°, I = +70°; K = 160, N = 4 sites); NE-1 (D = 72°, I = −70°; K = 320, N = 3 sites); and NE-2 (D = 31°, I = −24°; K = 67, N = 3 sites) with corresponding paleopole positions at CB-1 (16°N, 41°W; δp, δm = 6°, 7°); CB-2 (32°N, 97°W; δp, δm = 7°, 8°); and CB-3 (27°S, 96°W; δp, δm = 6°, 11°). The radiometric ages of these three remanence directions do not differ from each other by more than 50 Ma; these remanences are also present as low coercivity (5–25 mT) magnetizations in the Avalonian granites (10 sites). Antipole CB-3 agrees with other recently reported Early Devonian paleomagnetic results from the northern Appalachians. In contrast, the two other antipoles (CB-1 and CB-2) are located in southerly latitudes but do not differ significantly from poles of contemporaneous rocks in New Brunswick and Newfoundland. The "aberrancy" of southerly located Siluro-Devonian poles with respect to those in northern latitudes is discussed in the context of possible transcurrent motion of the "Acadia" displaced terrain with respect to cratonic North America. Presently available paleomagnetic data are not conclusive and cannot confirm or negate this possibility. The CB-1, CB-2, and CB-3 poles are interpreted as representing rapid apparent polar wander with respect to Cape Breton Island during Siluro-Devonian time.In the older Cambrian granites, pole CB (37°N, 176°E; δp, δm = 2°, 3°), derived from a high coercivity (20–70 mT) mean remanence direction NW (D = 318°, I = +15°; K = 298, N = 10 sites), probably corresponds to the Avalonian Orogeny. Further ...